Integrating Augmented Reality and Zero Waste Content in EFL Instruction: A Need Analysis Study - Fasya, Nadira Mutiara; Silvhiany, Sary; Eryansyah, Eryansyah (Edukasi, 2026)
Environmental literacy is crucial to overcome sustainability issues such as zero waste, especially in educational environments. This study evaluates the needs of students for augmented reality (AR) based zero waste content to improve environmental literacy in an English as a Foreign Language (EFL) context at MAN 2 Palembang. A descriptive quantitative design was employed using a needs analysis approach with 92 eleventh grade students. Data were collected through a questionnaire assessing environmental knowledge, attitudes, material needs, familiarity with AR technology, and the demand for AR-based learning media. Descriptive statistical analysis revealed distinct patterns across five indicators: Environmental Material Needs had the lowest mean score (M = 3.02, SD = 0.73), followed by Environmental Attitude and Responsibility (M = 3.41, SD = 0.34), and Environmental Knowledge and Awareness (M = 3.63, SD = 0.42). In contrast, AR-related indicators received higher mean scores, with AR Technology Knowledge attaining the highest (M = 3.88, SD = 0.39) and the Need for AR Based Learning Media showing strong support (M = 3.78, SD = 0.50). Furthermore, 58.7% of respondents indicated a high need for AR based learning media, while only 6.5% expressed low needs. These findings suggest that integrating zero waste content with AR based learning media can effectively support environmental literacy in EFL education. Practically, the results offer educators and curriculum developers evidence based guidance for creating contextually relevant and enhanced environmental learning materials that align students' technological readiness with their need for meaningful environmental content.